Occurrence and the ecological implication of a tropical anguillid eel Anguilla marmorata from peninsular Malaysia - Abdul Kadir, Siti Raudah; Abdul Rasid, Mohamad Hafiz Farhan; Kwong, Kok Onn; Wong, Li Lian; Arai, Takaomi (ZooKeys, 2017)
Recent studies suggested that accurate species identification in the tropical anguillid eels based on morphological examination requires confirmation by molecular genetic analysis. Previous studies found that two tropical anguillid eels, Anguilla bicolor bicolor and A. bengalensis bengalensis, were found in peninsular Malaysia (West Malaysia) based on morphological and molecular genetic analyses. This study is the first record of A. marmorata in peninsular Malaysia confirmed by both morphological and molecular genetic analyses. The present study also suggests that accurate tropical eel species identification is difficult by morphological identification alone; therefore, molecular genetic analysis is needed for precise species confirmation.